A Critical Discourse Analysis of the Representation of Self and Other in Prophetic Hadith - Ahmed, Prof. Muhammed Badeaꞌ Ahmed; Mahmood, Asst. Lect. Ruqayah Issa Mahmood (Sulaimani Journal for Humanities, 2026)
The diversity of societies in terms of race, ethnicity, religion, etc., the demographic changes all over the world, and the existence of minorities lead to what is called sthe elf and other constitution. The interdependence between self and other usually brings them into one context; that is, when there is 'we', it means that there is 'they' and vice versa. Usually, religious identities and ideologies are investigated in terms of the status quo or the way they are represented in mass media from a political viewpoint. In religious discourse, they seem to have received less attention from linguists. Therefore, the scarcity of linguistic research on the socio-religious self and others, particularly in Prophetic Hadith, is the key factor that necessitates this study. Besides, the potential of CDA approaches would contribute to illustrating the representation of self and other in such non-political discourse. This research attempts to investigate the socio-religious representation of self and other in Prophetic Hadith, aiming at investigating identities referred to through the linguistic structures and strategies which are employed in Prophetic Hadiths and examining the potential of employing a critical theory in religious discourse analysis. It is hypothesized that the nature of domination in Islamic society exhibits that the Islamic identity can be shown through the concrete and collective observances of Muslims. Pronouns not only refer but also function to show the limitations and boundaries between self and other in the selected texts. The paper concludes that identities and ideologies are manifested in various ways; they are expressed explicitly or implicitly, positively or negatively, generally or specifically, by concrete or abstract practices, personally or collectively, based on self or in relation to others. The nature of domination affects Muslims' identity. That is, the dominant nature of sthe elf in Prophetic Hadiths establishes concrete and collective practices to judge its members.
Keywords: Self; other; ideology; religious identity; Prophetic Hadith